Sleep duration change across breast cancer survivorship: associations with symptoms and health-related quality of life - Alfano, Catherine M. (2011)
PURPOSE: Sleep duration among breast cancer survivors correlates with fatigue, depression, and health-related quality of life (HRQOL); however, this has not been studied longitudinally. This study investigated patterns of sleep duration change across the early breast cancer survivorship period, their demographic and clinical predictors, and their relationships with subsequent cancer-related symptoms and HRQOL. METHODS: Breast cancer survivors (n=572), were assessed 6 months post-diagnosis (current sleep & retrospective reports of pre-diagnosis sleep), 30 months post-diagnosis (sleep), and 39 months post-diagnosis (symptoms, HRQOL). Sleep duration change was determined by examining sleep at each time point in relation to published norms. Analysis of variance and logistic regression models tested demographic and clinical differences between the sleep change groups; linear regression models tested differences in symptoms and HRQOL. RESULTS: Half of the survivors reported no sleep duration change over time; however, 25% reported sleep changes indicating a temporary (5.6%), late-occurring (14%), or sustained (5.9%) change. Survivors reporting sustained or temporary sleep changes were more likely to have been treated with chemotherapy (OR=2.62, p<.001) or gained weight after diagnosis (OR=1.82, p=.04) than those with no sleep change. Sustained sleep changes were related to greater subsequent severity, affective, and sensory aspects of fatigue (βs=2.0, 2.3, 1.8; all p <.0001) and lower vitality (β=−10.8, p=.005). CONCLUSIONS: Survivors treated with chemotherapy and those who gain weight after diagnosis may have increased risk for sustained sleep duration changes, which may increase their fatigue. These results point to the need for routine assessment of sleep as part of survivorship care.